Influencing public trust in central banks: Identifying who is open to new information - Bernd Hayo; Pierre-Guillaume Méon (Philipps-University Marburg, School of Business and Economics, 2022)
Using a randomized controlled trial in a 2018 survey of a representative sample of the German population, we study whether providing information about the European Central Bank's (ECB) inflation record in comparison to its inflation target affects people's trust in the central bank. In the treatment, administered to half of the roughly 2000 respondents, a graph of the annual inflation rate in the euro area from 1999 to 2017 and the ECB's 2% inflation target was shown to respondents. We find that the treatment has, on average, no significant effect on the level of trust respondents have in the ECB or on the distribution of survey answers. However, the treatment increases trust in the ECB among respondents who report no preference for any political party. Within this group, the effect is strongest among those who reported biased beliefs about the inflation rate but knew that price stability is the ECB's objective and those who reported a low level of subjective and objective knowledge about monetary policy.
Keywords: E52; E58; Z1; 330; Central bank trust; European Central Bank; Central bank communication; Monetary policy; Germany; Household survey; RCT